Mazrui and His Critics - Paul Banahene Adjei (International Institute of Islamic Thought, 2005)
This work is a review essay of two books: Africanity Redefined: Collected Essays of Ali A. Mazrui, edited by Ali Alamin Mazrui, Ricardo Rene Laremont, Tracia Leacock Seghatolislami, Michael A. Toler, and Fouad Kalouche (Africa World Press: 2002) and Governace and Leadership: Debating the African Condition: Ali Mazrui and His Critics, edited by Alamin M. Mazrui and Willy Mutunga (Africa World Press: 2003) These are the first two volumes in a three-volume work dealing with the correspondence among Ali Mazrui and his opponents, as well as his supporters, on issues relating to Africa. Mazrui, a Kenyan scholar, is currently Albert Schweitzer professor in humanities and director of the Institute of Global Cultural Studies, Binghamton University, State University of New York. An Oxford scholar, he is also Albert Luthuli professor-at-large in humanities and development studies at the University of Jos, Nigeria, as well as Andrew D. White professorat- large emeritus and senior scholar in Africana studies at Cornell University (www.islamonline.net). In addition, he has authored many publications and television and radio documentaries. Perhaps his best-known work in the West is his BBC radio and television documentary series “The Africans,” which was co-produced by the BBC and the public television station WETA. Writing on Mazrui, Sulayman Nyang of Howard University states: Ali Mazrui is a controversial but independent and original thinker. He is a master word-monger and certainly does not belong to that class of men who lament that words fail them. …It is because of his conjurer’s ability to negotiate between the realm of serious issues and the province of ...